Lithosphere Destabilization and Small‐Scale Convection Constrained From Geophysical Data and Analogical Models. (19th March 2021) - Adam, C.; Vidal, V.; Pandit, B.; Davaille, A.; Kempton, P. D.
Abstract: The destabilization of oceanic lithosphere by small scale convection at its base is important for providing a holistic picture of mantle/lithosphere coupling. We use three highly resolved tomography models to characterize the base of the oceanic lithosphere in the Pacific Ocean. Regions associated with abnormally thick lithosphere are associated with seafloor older than 100 Ma and are elongated parallel to the direction of present‐day Pacific plate motion. They are correlated with bathymetric lows and negative geoid anomalies (for l = 10–39 and l = 14–39), which can be accounted for by dynamic topography. They do not correlate with volcanic features. We interpret these regions of thickened lithosphere as evidence for sites of lithospheric instabilities where denser lithosphere detaches and sinks into the underlying mantle. To understand the phenomena at the origin of these lithospheric "drips, " we performed laboratory experiments. Fluids with different properties are heated from one side to generate a large‐scale convection and cooled from the top. This configuration results in the generation of small‐scale convection at the base of the upper cold thermal boundary layer. The experimental results show the existence of two possible structures: instabilities organized into longitudinal rolls, aligned in the direction of the large‐scale motion and 3D, time‐dependent cold plumes that drip from the base of the lithosphere and are sheared away by the large‐scale flow. The 3D plume morphology is similar to what we observe in tomography models. This provides insights into the phenomenology at the origin of the lithospheric drips observed in the geophysical data. Key Points: We use highly resolved tomography models to characterize the base of the oceanic lithosphere in the Pacific Ocean Regions associated with anomalous thick lithosphere correlate with bathymetry and geoid anomalies, and the plate kinematics The characteristics of lithospheric instabilities characterized from geophysical data correlates with the results of experimental models